Meaning of Numeral and Number System and Formulation of Roman Numerals Corresponding to Decimal Numbers - Saud, Dal Bahadur (Journal of Durgalaxmi, 2022)
The primary objective of the paper is to review the definition of number system adopting the basic and general way of formation of number in any existing number system like Egyptian, Roman, and Hindu-Arabic number system which played and are playing vital role for development of today's existing number system. But secondary aim of this article is to analyze and synthesize on Roman number system in various aspects and then to formulate structural stands to create Roman numbers corresponding to Hindu-Arabic (Decimal) numerals/numbers.